The words of war: Four days of the Chilean October 2019 - Arancibia Hurtado, Camilo (2022)
On September 4, 2022, the proposal for a New Constitution emanating from the Chilean Constitutional Convention was rejected and this has been explained in various ways. An interesting approach is the one that can arise from the Law and Literature approach, specifically, its category of "Law as literature". If a Magna Carta is the instrument where the most relevant legal words for a country are enshrined, it may be useful to carry out a philological examination of the words of the revolt of October 18, 2019, a fact that paved the way for the demand for a New Constitution. For this, I will resort to my own Political Journal in order to focus on the beginning of the outbreak, where with regard to the word "war", I maintain that there was an appearance of Chilean citizenship with characteristics that made possible a political interpretation of the phenomenon in key friend enemy. I will argue that the word "war" seeped into the word politics and may have influenced the word constitutional. To describe that appearance of Chilean citizenship during the outbreak, I will use the formulation of the question "Who am I?" of Hannah Arendt, of her reflections on the appearance in the public space and the division between friends and enemies of Carl Schmitt. I will end with some conclusions.